Evolving Communication Skills: The Impact of Transactional Analysis Counseling - Cania, Lita Fitara; Netrawati, Netrawati; Ardi, Zadrian (Jurnal Bimbingan dan Konseling Terapan, 2024)
This article provides a comprehensive exploration of the role and effectiveness of Transactional Analysis counseling in improving interpersonal communication skills. By synthesizing studies and theories from a variety of sources, the article presents insights into the intrinsic aspects of Transactional Analysis counseling and its applicability in various scenarios. A highlight of the article is its emphasis on role-play techniques and their positive impacts on communication skills enhancement. Further, the role of interpersonal communication in building relationships and understanding within diverse societies is also analyzed. The importance of emotional intelligence, conflict management, and social interaction in the context of Transactional Analysis counseling is underscored. The review reveals that Transactional Analysis counseling can be a potent tool to enhance self-awareness, tackle adolescent developmental issues, and minimize bullying behavior. It emphasizes that a counselor's role, built on Transactional Analysis approach, is vital in fostering improved interpersonal communication.